2011
DOI: 10.1089/end.2010.0737
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Intrarenal Surgery Versus Percutaneous Nephrolithotomy in the Management of Lower-Pole Renal Stones with a Diameter of 15 to 20 mm

Abstract: PCNL and RIRS are safe and effective methods for medium-sized LP calculi. For selected patients, RIRS may represent an alternative therapy to PCNL, with acceptable efficacy and low morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
105
4
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(123 citation statements)
references
References 25 publications
2
105
4
12
Order By: Relevance
“…According to our results, the stone-free rate of this surgery was 81.2% and between 70% and 97% in the international literature. [4][5][6][7][11][12][13][14] These studies mentioned above showed that our results were consistent with the international literature. Up to date, no specific classification system has been described for per-operative complication of RIRS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to our results, the stone-free rate of this surgery was 81.2% and between 70% and 97% in the international literature. [4][5][6][7][11][12][13][14] These studies mentioned above showed that our results were consistent with the international literature. Up to date, no specific classification system has been described for per-operative complication of RIRS.…”
Section: Discussionsupporting
confidence: 93%
“…In a study by Bozkurt et al, stone-free and per-operative complication rates were reported as 89.2% and 5.4% (grade 1 and 2) in 37 patients who underwent RIRS. 12 In a review by Breda and Angerri, 10 studies were assessed and overall stonefree and per-operative complication rates were reported as 89.3% and 8%, respectively. 7 They noted that major complication rate was 1.9%.…”
Section: Discussionmentioning
confidence: 99%
“…RIRS is a reasonable alternative to PCNL and ESWL in lowvolume lower calyx stones, because it has a lower complication rate compared with PCNL and a stone-free rate similar to that of ESWL. Bozkurt et al [8] compared the results of 42 PCNL and 37 RIRS patients treated for clearance of renal stones with sizes of 1.5-2 cm. They reported the success rate as 92.8% for PCNL and 89.2% for RIRS.…”
Section: Discussionmentioning
confidence: 99%
“…At the other site, the guidelines recommend PCNL or fURS for stones >15mm that are located in the lower pole, given that SWL has limited efficacy in the treatment of these stones (1). Despite these recommendations, there have been various published articles reporting high success rates with fURS, even for high stone burdens in any kidney location (13)(14)(15). The retrograde intrarenal stone surgery is gaining more popularity day by day, given that it offers similar SFR and lower complication rates compared with PCNL, as well as and higher success rates compared with SWL (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%